A temporary indwelling intravascular aphaeretic system for in vivo enrichment of circulating tumor cells - Tae Hyun Kim (Nature Portfolio, 2019)
Ex vivo methods of circulating tumor cell (CTC) isolation use small blood volumes, limiting sensitivity and introducing analytical inaccuracies. The authors describe a proof-of-concept study of an in vivo aphaeresis system that continuously collects CTCs from a peripheral vein over several hours.